2014
DOI: 10.1152/ajprenal.00454.2014
|View full text |Cite
|
Sign up to set email alerts
|

Akt recruits Dab2 to albumin endocytosis in the proximal tubule

Abstract: Proximal tubule epithelial cells have a highly sophisticated endocytic machinery to retrieve the albumin in the glomerular filtrate. The megalin-cubilin complex and the endocytic adaptor disabled-2 (Dab2) play a pivotal role in albumin endocytosis. We previously demonstrated that protein kinase B (Akt) regulates albumin endocytosis in the proximal tubule through an interaction with Dab2. Here, we examined the nature of Akt-Dab2 interaction. The pleckstrin homology (PH) and catalytic domains (CD) of Akt interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
(46 reference statements)
2
27
0
Order By: Relevance
“… In order to examine a possible direct interaction between cytoplasmic tail (CT) of megalin and AS160, in-vitro pull-down experiments were carried out. Cytoplasmic tail of megalin was cloned and GST-megalin fusion protein was generated as outlined in the methods section [ 21 ]. Approximately 100μg of GST, GST-megalin CT immobilized on GSH-Sepharose were incubated with HKC-8 cell lysate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… In order to examine a possible direct interaction between cytoplasmic tail (CT) of megalin and AS160, in-vitro pull-down experiments were carried out. Cytoplasmic tail of megalin was cloned and GST-megalin fusion protein was generated as outlined in the methods section [ 21 ]. Approximately 100μg of GST, GST-megalin CT immobilized on GSH-Sepharose were incubated with HKC-8 cell lysate.…”
Section: Resultsmentioning
confidence: 99%
“…We reported that protein kinase B (Akt), a pivotal protein in insulin signaling, mediates albumin endocytosis in proximal tubule epithelial cells through its interaction with the endocytic proteins [ 20 21 ]. In this study, we examined the effect of insulin induced Akt activation on albumin endocytosis in proximal tubule epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of the phosphorylated serine residues on Dab2 caused its loss from the cell surface and reduced albumin uptake in human HKC-8 cells (94). Additionally, overexpression of Akt/PKB stimulated albumin uptake, whereas knockdown had the converse effect (94, 95).…”
Section: Organization Of the Proximal Tubule Apical Endocytic Pathwaymentioning
confidence: 99%
“…Mutation of the phosphorylated serine residues on Dab2 caused its loss from the cell surface and reduced albumin uptake in human HKC-8 cells (94). Additionally, overexpression of Akt/PKB stimulated albumin uptake, whereas knockdown had the converse effect (94, 95). Angiotensin II, acting via the AT 2 receptor, also stimulates albumin endocytosis in LLC-PK1 cells by the activation of Akt/PKB via its upstream regulator phosphatidylinositol 3-kinase (PI3K) (96).…”
Section: Organization Of the Proximal Tubule Apical Endocytic Pathwaymentioning
confidence: 99%
“…Megalin was recently described as a fast-recycling, long-lived receptor, which completes its cycle through the different endosomal compartments in ϳ10 min (34). Different mechanisms were shown to regulate megalin trafficking, such as adaptor proteins ARH (35) and Dab2 (36), and GSK3␤-dependent phosphorylation in the PPPSP domain (37), explaining the fast cycling kinetics of this receptor. Here, we demonstrated, both in vitro and in vivo, that…”
Section: O-glcnacylation Inhibits Pt Protein Reabsorption In Shrsmentioning
confidence: 99%